2016
DOI: 10.1063/1.4954022
|View full text |Cite
|
Sign up to set email alerts
|

Driving-induced multistability in coupled chaotic oscillators: Symmetries and riddled basins

Abstract: We study the multistability that results when a chaotic response system that has an invariant symmetry is driven by another chaotic oscillator. We observe that there is a transition from a desynchronized state to a situation of multistability. In the case considered, there are three coexisting attractors, two of which are synchronized and one is desynchronized. For large coupling, the asynchronous attractor disappears, leaving the system bistable. We study the basins of attraction of the system in the regime o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…8 where the boundary points seemed to span a two dimensional region in the two dimensional slice of the phase space. Our results also agree with previous studies of riddled basins of attraction where the uncertainty exponent α has been reported to be approximately zero 44 . Although the coupling strength chosen for Fig.…”
Section: Characteristics Of Basins Of Attractionsupporting
confidence: 93%
“…8 where the boundary points seemed to span a two dimensional region in the two dimensional slice of the phase space. Our results also agree with previous studies of riddled basins of attraction where the uncertainty exponent α has been reported to be approximately zero 44 . Although the coupling strength chosen for Fig.…”
Section: Characteristics Of Basins Of Attractionsupporting
confidence: 93%
“…In the coupled system, the basin structure of the different attractors is complex [33]: there is a finite probability that two randomly selected nearby initial conditions will asymptote to different attractors (A ∓ and A 0 ). The measured uncertainty exponent lies close to zero, suggesting that the basins are effectively riddled (figure not shown here), but measures such as the transverse Lyapunov exponent and scaling laws [27] have not been straightforward to calculate.…”
Section: Basins Of Attractionmentioning
confidence: 99%
“…At ε 1 = 0.023 the basin is completely interwoven in a complex manner and is completely intertwined for large volumes and it is very likely that the basin will be even more complicated for larger N . In general, the basin structure of different attractors in coupled systems is complex [26,27]. Thus there is finite probability that two randomly selected nearby initial conditions will asymptote to different regimes that may be synchronized or desynchronized.…”
Section: Basin Of Attraction and Lyapunov Exponentmentioning
confidence: 99%